HUBUNGAN ANTARA USIA IBU DAN PARITAS DENGAN KEJADIAN PERDARAHAN POSTPARTUM : A SYSTEMATIC LITERATURE REVIEW - Endah Dwi Pratiwi (STIKes CHMK, 2023)
Bleeding is an important problem because it is related to maternal health which can cause death. One of them is postpartum hemorrhage. The aim was to find out to conduct a theoretical and literature review of the relationship between maternal age and parity (number of deliveries) with the incidence of postpartum hemorrhage. Journal searches were carried out electronically using several databases, namely: DOAJ, Garuda Portal and Google Scholar from 2012-2020. The keywords are or age and parity, post partum bleeding events. The research results selected articles from 2 international journals and 5 national journals concluded that there is a relationship between maternal age and parity (number of deliveries) with the incidence of postpartum hemorrhage. Keywords: Maternal age, parity and postpartum hemorrhage